2017
DOI: 10.1063/1.4983344
|View full text |Cite
|
Sign up to set email alerts
|

Dewetting and spreading transitions for active matter on random pinning substrates

Abstract: We show that sterically interacting self-propelled disks in the presence of random pinning substrates exhibit transitions among a variety of different states. In particular, from a phase separated cluster state, the disks can spread out and homogeneously cover the substrate in what can be viewed as an example of an active matter wetting transition. We map the location of this transition as a function of activity, disk density, and substrate strength, and we also identify other phases including a cluster state,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…The case 0 < α + β < 1 is analogous to the finding of Chechkin and colleagues [11,14,82,15,72]. On the other hand, the case 1 < α + β < 2 can depict many phases in [76] for certain pinning forces at low disk activity. The probability density (3.3) transition regime in the short-time limiting included in the Cattaneo-type equation is clear in the blue curve, where 0 < α + β < 1.…”
Section: Generalised Cattaneo Equation Of Type Isupporting
confidence: 70%
See 1 more Smart Citation
“…The case 0 < α + β < 1 is analogous to the finding of Chechkin and colleagues [11,14,82,15,72]. On the other hand, the case 1 < α + β < 2 can depict many phases in [76] for certain pinning forces at low disk activity. The probability density (3.3) transition regime in the short-time limiting included in the Cattaneo-type equation is clear in the blue curve, where 0 < α + β < 1.…”
Section: Generalised Cattaneo Equation Of Type Isupporting
confidence: 70%
“…The reader is also referred to generalisations of diffusion, Fokker-Planck, and diffusion-wave equations by introduction of a generalised memory kernel [73,74,75]. However, recent numerical simulations have shown different transitions from superdiffusion to subdiffusion which are not, in all cases, covered by equation (1.7), see e.g., quasiperiodic interacting systems [38] and dewettingspreading-wetting transitions of self-propelled (run-and-tumble) clustered disks in a substrate with randomly placed pinning sites [76].…”
Section: Introductionmentioning
confidence: 99%
“…"Quite generally" one observes accumulation of active particles at a purely repulsive "hard" wall or impenetrable obstacles [2,23]. This has led to numerical searches for surface phase transitions in 2D models of active matter [24][25][26][27]. For a 2D lattice gas, hard walls lead to a completely wet state having θ ¼ 0 [27].…”
mentioning
confidence: 99%
“…Even in case of S<0, the film does not dewet immediately when located in a metastable state, e.g., when temperature is below Preprints (www.preprints.org) | NOT PEER-REVIEWED | Active matter wetting transition. Sándor et al (2017) showed that, in the presence of random pinning substrates, sterically interacting self-propelled disks exhibit transitions among different states. In particular, we are in front of an Preprints (www.preprints.org) | NOT PEER-REVIEWED |…”
mentioning
confidence: 99%
“…example of active matter wetting transition: starting from a phase of separated cluster state, the disks can spread out and homogeneously cover the substrate. This transition is regulated by disk density, substrate strength, cluster size (which dips at the wetting-dewetting transition) and fraction of sixfold coordinated particles (which drops when dewetting occurs) (Sándor et al, 2017).…”
mentioning
confidence: 99%